Conservation of chicken male germline by orthotopic transplantation of primordial germ cells from genetically distant donors†. Issue 1 (13th April 2019) - Mucksová, Jitka; Reinišová, Markéta; Kalina, Jiří; Lejčková, Barbora; Hejnar, Jiří; Trefil, Pavel
Abstract: Successful derivation and cultivation of primordial germ cells (PGCs) opened the way to efficient transgenesis and genome editing in the chicken. Furthermore, implantation of male PGCs from non-chicken galliform species into the chicken embryos resulted in cross-species germline chimeras and viable offspring. We have recently improved the PGC technology by demonstrating that chicken male PGCs transplanted into the testes of adult cockerel recipients mature into functional sperms. However, the availability of this orthotopic transplantation for cross-species transfer remains to be explored. Here we tested the capacity of genetically distant male PGCs to mature in the microenvironment of adult testes. We derived PGCs from the Chinese black-bone Silkie and transplanted them into infertile White Leghorn cockerels. Within 15–18 weeks after transplantation, we observed restoration of spermatogenesis in recipient cockerels and production of healthy progeny derived from the transplanted PGCs. Our findings also indicate the possibility of cross-species orthotopic transplantation of PGCs. Thus, our results might contribute to the preservation of endangered avian species and maintaining the genetic variability of the domestic chicken. Abstract : Chicken PGCs derived from genetically distant embryo are able to produce viable spermatozoa when transplanted into adult testes.